Study on the coupling role and forecasting of energy-economy-environment triple system based on system dynamics approach, taking Inner Mongolia autonomous region as an example - Zhu, Hongtao; Zhu, Yue; Hu, Bo; Qiao, Yongfeng; Liu, Luxia (Frontiers in Environmental Science, 2025)
The sustainable development of Inner Mongolia, particularly the coordinated development of energy, economy, and environment, plays a crucial role in shaping energy strategies and environmental protection policies for both Inner Mongolia and China. Based on this, the study focuses on the energy-economy-environment coupling in Inner Mongolia, employing system dynamics for multi-scenario simulations. The findings reveal: (1) the overall coupling coordination degree is improving, with the energy-environment friendly scenario yielding the best results; (2) industrial pollution and energy consumption are significant factors influencing coupling coordination; (3) addressing energy consumption and achieving carbon neutrality are long-term challenges for Inner Mongolia’s sustainable development. Therefore, Inner Mongolia should optimize its industrial structure, promote high-tech and low-carbon industries, improve energy efficiency, develop renewable energy, and strengthen pollution control and carbon emission management to achieve sustainable development across its economy, energy, and environment.